2016
DOI: 10.1590/2175-353920150202972
|View full text |Cite
|
Sign up to set email alerts
|

Motivação intrínseca e extrínseca: diferenças no sexo e na idade

Abstract: ResumoA orientação motivacional é um determinante crítico do nível e da qualidade da aprendizagem. Este estudo investigou os níveis de orientação motivacional e as possíveis diferenças entre idade e sexo em 142 crianças de nove e 10 anos alunos de escolas públicas. A "Scale of Intrisic versus Extrinsic Orientation in Classroom" de Harter (1980) foi o instrumento utilizado para a coleta de dados. A escala foi aplicada individualmente e lidaem voz alta pela pesquisadora para melhor compreensão da criança. Os re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 20 publications
0
10
1
18
Order By: Relevance
“…In the evaluation of intrinsic motivation in relation to the gender of the students, this study failed to find any association, unlike other research 8,15,16,[18][19][20][21] , which, although using different methodologies, found greater motivation among females. It is known that female students tend to perceive their teacher as providing more support than male students do, and this perception measured by gender may differentiate motivation and emotional experience 21 .It is speculated that our results derive from the learning methodology adopted at the school studied, by exposing students, regardless of gender, to the factors related to the development of motivation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the evaluation of intrinsic motivation in relation to the gender of the students, this study failed to find any association, unlike other research 8,15,16,[18][19][20][21] , which, although using different methodologies, found greater motivation among females. It is known that female students tend to perceive their teacher as providing more support than male students do, and this perception measured by gender may differentiate motivation and emotional experience 21 .It is speculated that our results derive from the learning methodology adopted at the school studied, by exposing students, regardless of gender, to the factors related to the development of motivation.…”
Section: Discussioncontrasting
confidence: 99%
“…Considering the factors that influenced the student's intrinsic motivation [15][16][17][18][19][20][21]24,25 , the variables gender, age, marital status, financial dependents, attempts at the entry exam, current semester of course, prior undergraduate training, living with parents, choice of course by need for health care, by parental influence or pressure, were studied to analyse possible factors associated to intrinsic motivation. A reference category was considered to be with an outcome that presented a greater frequency (intrinsic motivation with a mean score > 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essa diferença pode ser compreendida por uma perspectiva de gênero, que pode sugerir que as meninas precisam aplicar esforços para serem reconhecidas por suas habilidades, para conseguir uma boa posição social e serem reconhecidas no mercado de trabalho como capazes de contribuir na sociedade. Ainda que a literatura apresente estudos que demonstram diferença entre meninas e meninos quanto à motivação para aprender (DeBacker & Nelson, 2000) e outros em que não há diferença (Pansera, Valentini, Souza, & Berleze, 2016;Schulze & Van Heerden, 2015), a diferença encontrada no estudo atual pode estar relacionada às questões de gênero que, muitas vezes, podem produzir o receio de fracasso e de punição por não atenderem às expectativas.…”
Section: Discussionunclassified
“…No estudo de Boruchovitch (2008), o aumento da idade está associado ao aumento da motivação tanto da intrínseca como da extrínseca. Ainda sobre a diferença, por faixa etária, na motivação, estudo realizado por Pansera et al (2016) não encontrou diferenças na motivação entre crianças de 9 a 10 anos.…”
Section: Discussionunclassified